Pengaruh Reggio Emilia Approach dalam Bermain Peran dan Bererita terhadap Kemampuan Bahasa Anak - Azizah Amal; Muhammad Akil Musi; Hajerah Hajerah (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2019)
AbstractThe purpose of this study was to determine the effect of applying the Reggio Emilia Approach in role-playing and telling stories of early childhood language skills. The type of research used in the study was an experiment with a quasi-experimental design. The influence of the application of the Reggio Emilia Approach can be seen by comparing the average score obtained from the language proficiency test between the experimental groups applying the Reggio Emilia Approach in role play with the average score obtained from the control group using the Reggio Emilia Approach approach in storytelling. The conclusion is that the application of the Reggio Emilia Approach in role-playing and storytelling influences early childhood language skills.Keywords: Reggio Emilia Approach, Role Playing, Children's Language Ability. Abstrak Tujuan penelitian ini adalah mengetahui pengaruh penerapan Reggio Emilia Approach dalam bermain peran dan bercerita terhadap kemampuan bahasa anak usia dini. Jenis penelitian yang digunakan dalam penelitian adalah eksperimen dengan quasi-experimental design. Pengaruh penerapan Reggio Emilia Approach dapat dilihat dengan membandingkan rata-rata perolehan skor hasil tes kemampuan bahasa antara kelompok eksperimen yang menerapkan Reggio Emilia Approach dalam bermain peran dengan rata-rata perolehan skor hasil tes kelompok kontrol yang menggunakan pendekatan Reggio Emilia Approach dalam bercerita. Hasil kesimpulannya adalah penerapan Reggio Emilia Approach dalam bermain peran dan bercerita berpengaruh terhadap kemampuan bahasa anak usia dini.Kata Kunci: Reggio Emilia Approach, Bermain Peran, Kemampuan Bahasa Anak.